2023
DOI: 10.1002/smll.202302464
|View full text |Cite
|
Sign up to set email alerts
|

3D Hollow Hierarchical Porous Carbon with Fe‐N4‐OH Single‐Atom Sites for High‐Performance Zn‐Air Batteries

Shilong Zhou,
Chao Chen,
Jiawei Xia
et al.

Abstract: The development of innovative and efficient Fe‐N‐C catalysts is crucial for the widespread application of zinc‐air batteries (ZABs), where the inherent oxygen reduction reaction (ORR) activity of Fe single‐atom sites needs to be optimized to meet the practical application. Herein, a three‐dimensional (3D) hollow hierarchical porous electrocatalyst (ZIF8@FePMPDA‐920) rich in asymmetric Fe‐N4‐OH moieties as the single atomic sites is reported. The Fe center is in a penta‐coordinated geometry with four N atoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It can be concluded that the bimetal doped method can increase the defect degree of the catalyst, which can help adsorb oxygen and promote ORR. 40 BET test is usually used to analyze the pore structure of the catalyst. Figure 2c,d shows the nitrogen adsorption−desorption curves and pore size distributions of the three catalysts, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that the bimetal doped method can increase the defect degree of the catalyst, which can help adsorb oxygen and promote ORR. 40 BET test is usually used to analyze the pore structure of the catalyst. Figure 2c,d shows the nitrogen adsorption−desorption curves and pore size distributions of the three catalysts, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the I D / I G values of the three samples, FeNi-NPC-1000 (1.11) has the highest defect degree compared to those of Fe-NPC-1000 (1.09) and Ni-NPC-1000 (0.995). It can be concluded that the bimetal doped method can increase the defect degree of the catalyst, which can help adsorb oxygen and promote ORR . BET test is usually used to analyze the pore structure of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, ORR and ZAB performances of Fe-SA/NSC also approach the best levels observed in these reported Fe-based catalysts (Figure f and Table S5). ,, …”
Section: Resultsmentioning
confidence: 99%
“…[12] The electronic structure of the central metal atom is adjusted by the axial coordination of the OH groups, which could optimize the adsorption-free energy of the Fe center, reducing the H 2 O 2 yield of ORR, and thereby improving the stability of the Fe-N-C catalyst. [13] However, it is difficult to achieve an outstanding improvement in ORR performance by introducing solely oxygen-containing functional groups. In addition, a new asymmetric planar tetra-coordinated configuration is also rebuilt by extra heteroatoms (B, S, P, etc.)…”
Section: Introductionmentioning
confidence: 99%